Octabenzone Isolated from Saharan Myrtle Leaves (Myrtus nivellei) - Mansour, Amira; Rahili, Ghania; Roza, Orsolya; Chemat, Smain (Natural Products Journal, The, 2021)
Background: The Algerian Saharan plants are plants of terrestrial origin, which during their evolution have adapted to the Algerian south ecosystem. By their particular ecological and evolutionary position, it is possible that these endemic plants also selected specific secondary metabolites with original chemical and biological characteristics. Objective: Phytochemical investigation of ethyl acetate and n-butanol extracts of M. nivellei leaves. Methods: Air-dried and coarsely powdered leaves were macerated with 80% methanol. The methanol extract diluted with distilled water was successively extracted with hexane, ethyl acetate and n- BuOH. The ethyl acetate and n-butanol extracts were fractionated by sephadex (LH-20) column using MeOH as eluent. Fraction 1 from ethyl acetate extract was chromatographed by preparative TLC to give pure compound (1). Fractions 4 and 5 from n-butanol extract were chromatographed by RPHPLC over a C18 column using MeOH/H2O (4:6, v/v) as solvent system. Fraction 4 gave compounds 3 (1.5 mg) and 4 (1.1 mg), fraction 5 gave compound 2 (5.5 mg). Structural elucidation was established by a combination of one- and two-dimensional NMR techniques, and mass spectrometry. Results: The investigation of ethyl acetate and n-butanol extracts of M. nivellei leaves allowed the isolation for the first time of Octabenzone (1) which was never reported before along with three known flavonols, myricetin 3-O-β-D-(6”-galloyl)galactoside (2), quercetin 3-O-β-D-(6”- galloyl)galactoside (3) and myricetin 3-O-arabinoside (4). Conclusion: These results suggested that the leaves of M. nivellei stand as a promising natural source for sunscreen products such as octabenzone. In combination with its richness of phenolic compounds, these observations lead us toward further studies concerning M. nivellei biological activity against skin damages and skin cancer.
Keywords: Saharan myrtle